0191 Individual Differences In Sleep Log Compliance And Agreement With Wrist Actigraphy: A Longitudinal Study Of Naturalistic Sleep In Healthy Adults. (27th April 2018) - Vettel, J M; Thurman, S M; Wasylyshyn, N; Roy, H; Lieberman, G; Asturias, A; Okafor, G; Elliot, J; Giesbrecht, B; Grafton, S T; Garcia, J O
Abstract: Introduction: There is extensive laboratory research on acute sleep deprivation and biological/cognitive functions, yet much less is known about naturalistic patterns of sleep loss and the impact on daily or weekly performance of an individual. Longitudinal studies provide an avenue to understand direct relationships between naturalistic sleep and fluctuations in human health and performance. Methods: The present study used wrist actigraphy and sleep log diaries to obtain daily measurements of sleep-related variables from 30 healthy adults for up to 16 consecutive weeks. We used non-parametric Bland-Altman analysis and correlation coefficients to calculate agreement between variables including sleep onset time, sleep offset time, sleep onset latency, number of awakenings, wake after sleep onset, and total sleep time. To better understand individual variability, we examined compliance data on the submission of daily sleep logs as well as performance data across several diverse cognitive tasks. Results: Overall, we found strong agreement for sleep onset and sleep offset times, but relatively poor agreement for variables related to night wakefulness. Compliance tended to decrease significantly over time according to a linear function, but there were also substantial individual differences in compliance that could help explain variability in agreement. Individuals who were consistently more compliant over time also tended to show the best agreement between objective measures and self-report. Individual variability in sleep onset time often revealed the strongest relationship with differences in task performance. Conclusion: These results demonstrate convergent validity in measuring sleep onset and sleep offset times with actigraphy/sleep logs across several months in a natural environment, but also recommend caution interpreting variables related to night wakefulness and self-report data from individuals showing relatively poor compliance. Support (If Any): This research was supported by the U.S. Army Research Laboratory.